Transient cold storage prior to normothermic liver perfusion may facilitate adoption of a novel technology - Ceresa, C; Nasralla, D; Watson, C; Butler, A; Coussios, C; Crick, K; Hodson, L; Imber, C; Jassem, W; Knight, S; Mergental, H; Ploeg, R; et al. (Wiley, 2019)
Clinical adoption of normothermic machine perfusion (NMP) may be facilitated by simplifying logistics and reducing costs. This can be achieved by cold storage of livers for transportation to recipient centers before commencing NMP. The purpose of this study was to assess the safety and feasibility of post–static cold storage normothermic machine perfusion (pSCS‐NMP) in liver transplantation. In this multicenter prospective study, 31 livers were transplanted. The primary endpoint was 30‐day graft survival. Secondary endpoints included the following: peak posttransplant aspartate aminotransferase (AST), early allograft dysfunction (EAD), postreperfusion syndrome (PRS), adverse events, critical care and hospital stay, biliary complications, and 12‐month graft survival. The 30‐day graft survival rate was 94%. Livers were preserved for a total of 14 hours 10 minutes ± 4 hours 46 minutes, which included 6 hours 1 minute ± 1 hour 19 minutes of static cold storage before 8 hours 24 minutes ± 4 hours 4 minutes of NMP. Median peak serum AST in the first 7 days postoperatively was 457 U/L (92‐8669 U/L), and 4 (13%) patients developed EAD. PRS was observed in 3 (10%) livers. The median duration of initial critical care stay was 3 days (1‐20 days), and median hospital stay was 13 days (7‐31 days). There were 7 (23%) patients who developed complications of grade 3b severity or above, and 2 (6%) patients developed biliary complications: 1 bile leak and 1 anastomotic stricture with no cases of ischemic cholangiopathy. The 12‐month overall graft survival rate (including death with a functioning graft) was 84%. In conclusion, this study demonstrates that pSCS‐NMP was feasible and safe, which may facilitate clinical adoption.